Validation of the scale of gender stereotypes in sexual risk behavior in men deprived of their liberty (European Journal of Health Research, 2017)
The purpose of this work was to validate the scale of gender stereotypes in sexual risk behavior in a population deprived of freedom (PDF). A total of 687 men with an average age of 26 belonging to a Social Rehabilitation Center of Mexico participated. They answered a scale of 20 items on gender stereotypes about sexual behavior; as well as 12 reagents of the scale of gender stereotypes of Rocha & Díaz-Loving (2005), in addition the psychometric properties are compared with university students of the original scale and the use of the condom in sexual relations was evaluated. The reagents were subjected to a factor analysis with varimax rotation, the internal consistency analysis and the convergent validity were obtained, finding suitable psychometric properties. With the validated scale, significant differences were found between those who use or not condom in their sexual relations, those who do not use it have more gender stereotypes. The results are discussed in terms of the importance of having valid and reliable instruments in PDF, as well as the influence of gender stereotypes on sexual behavior.
Keywords: validation; stereotypes; condom use